THE CAPACITY IMPROVEMENT OF EGG DUCK FARMERS IN DESA KOLAM THROUGH ENHANCING THEIR FINANCIAL MANAGEMENT AND ENTREPRENEURSHIP SKILL - Putra, Pasca Dwi (Universitas Negeri Medan, 2017)
AbstractThe purpose of community service is for training and counseling to duck farmers to plan and market their business to be better and can compete in the business world. In addition, the importance of financial management and entrepreneurship helps the farmers to plan their finances and marketing so that people can know the potential they have and see opportunities to develop the livestock business. The results of this dedication show that training and counseling of financial and entrepreneurial management helps farmers in financial planning such as feed and maintenance costs incurred, calculate the reasonable selling price of eggs, and plan future activities in developing the livestock business. Due to background education of farmers not from financial, so deep enough approach is required in explaining financial management and entrepreneurship as well as simple submission so that farmers can more easily understand the application of financial management concepts and entrepreneurship in the business world.Keywords: Financial Management, Entrepreneurship, Duck Farmers, Desa Kolam